Demographic, exposure and clinical characteristics in a multinational registry of engineered stone workers with silicosis. Issue 9 (3rd May 2022) - Hua, Jeremy Tang; Zell-Baran, Lauren; Go, Leonard H T; Kramer, Mordechai R; Van Bree, Johanna B; Chambers, Daniel; Deller, David; Newbigin, Katrina; Matula, Michael; Fireman, Elizabeth; Dahbash, Mor; Martinez-Gonzalez, Cristina; et al.
Abstract : Objectives: To investigate differences in workplace exposure, demographic and clinical findings in engineered stone (ES) workers from a multinational consortium using the Engineered Stone Silicosis Investigators (ESSI) Global Silicosis Registry. Methods: With ethics board approval in Israel, Spain, Australia and the USA, ES workers ages 18+ with a physician diagnosis of work-related silicosis were enrolled. Demographic, occupational, radiologic, pulmonary function and silica-related comorbidity data were compared cross-sectionally among countries using analysis of variance, Fisher's exact tests and logistic regression. Results: Among 169 ES workers with silicosis, most were men, with mean age 51.7 (±11.4) years. Mean work tenure in stone fabrication or masonry was 19.9 (±9.8) years. Different methods of case ascertainment explained some inter-country differences, for example, workers in Queensland, Australia with a state-based surveillance program were likely to be identified earlier and with shorter work tenure. Overall, 32.5% of workers had progressive massive fibrosis, the most severe form of dust-related pneumoconiosis, of whom 18.5% reported ≤10 years of work tenure. Lung function impairment including restriction, reduced diffusion capacity and hypoxaemia was common, as was autoimmunity. Conclusions: Findings from a multinational registry represent a unique effort to compare demographic, exposure and clinical information from ES workers with silicosis, and suggest a substantial emerging population of workers worldwide with severe and irreversible silica-associated diseases. This younger worker population is at high risk for disease progression, multiple comorbidities and severe disability. The ESSI registry provides an ongoing framework for investigating epidemiological trends and developing prospective studies for prevention and treatment of these workers.